Analysis of a Gamification Based on Bartle Profiles in a Virtual Learning Environment - Moraes, Daniel de Sousa; Guedes, Álan L. V.; Castro, Vinícius C.; Dias, Lukas H.; Soares Neto, Carlos de S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Computer Science courses are among the ones with the highest evasion rates. One factor is the lack of student engagement. This problem happens in both traditional courses as in the ones supported by a Virtual Learning Environment (VLE). One way to minimize this problem is the use of elements of games, a technique also known as gamification. In this paper, we present an analysis of a VLE gamification based on Bartle Profiles. More precisely, we: (1) classify students in these profiles; and (2) use gamification elements, related to each profile, to maximize the engagement. As a result, we present an experiment with 44 students from an introduction to algorithms course. We found evidence that the applied gamification was promising in promoting engagement.